Non-Severe COVID-19 Complicated by Deep Vein Thrombosis (DVT) - Rajabto, Wulyo; Priantono, Dimas (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Coronavirus Disease 2019 (COVID-19) displays various symptoms ranging from asymptomatic to life-threatening. Patients may present with typical respiratory infections or atypical symptoms. Non-severe COVID-19 encompasses mild and moderate cases, characterized by the absence of criteria for severe or critical illness, with mild cases not showing evidence of viral pneumonia or hypoxia and moderate cases maintaining SpO2 levels of at least 90% on room air.Case: We presented a COVID-19 case with the chief complaint of unilateral leg swelling. A 48-year-old male was admitted with the chief complaint of cramps and swelling of the left leg. He had a history of fever, cough, nausea, and vomiting. Laboratory studies showed elevated D-dimer. Doppler ultrasound shows signs of both proximal and distal deep vein thrombosis. CT pulmonary angiography excluded pulmonary embolism while the lung window image supported the diagnosis of COVID-19 pneumonia. Polymerase chain reaction (PCR) obtained from nasopharyngeal and oropharyngeal swabs confirmed COVID-19 infection.Discussion: We treated the patient with parenteral anticoagulation followed by direct oral anticoagulant upon discharge. The swelling improved as well as the patient’s clinical status. Thromboembolic complications have been credited as the culprit of high mortality in COVID-19. Systemic activation of coagulation in pulmonary and peripheral circulation contributed to life-threatening thrombotic complications. Our patient presented with COVID-19-associated proximal and distal DVT without pulmonary embolism.Conclusion: Prompt diagnosis of COVID-19 infection and acute DVT improves patient care. The hallmark of the management of VTE in COVID-19 patients is treatment with therapeutic dose parenteral anticoagulation followed by oral anticoagulant.